Outcomes of Robot-Assisted Laparoscopic Prostatectomy with a Posterior Approach to the Seminal Vesicle in 300 Patients - Yasui, Takahiro (Int Sch Res Notices, 2014)
Background. The goal of this study was to analyze the perioperative outcomes of robot-assisted laparoscopic radical prostatectomies (RALPs) performed at our center. Methodology. We retrospectively reviewed 300 consecutive patients with clinically localized prostate cancer who underwent RALP with a posterior dissection approach to the seminal vesicle between May 2011 and November 2013. The mean patient age was 67.2 ± 5.5 years (range: 41–78 years), and the mean prostate-specific antigen (PSA) concentration, at diagnosis of prostate cancer, was 9.16 ± 6.50 ng/mL (range: 2.20–55.31 ng/mL). Results. The median duration of robotic surgery was 160 min (mean: 165 ± 40 min; range: 75–345 min). Median estimated blood loss, including that in urine, was 200 mL (mean: 277 ± 324 mL; range: 4–3250 mL). Intraoperative and immediate postoperative complications occurred in 3.0% of patients; 4 patients required allogeneic blood transfusion. As a measure of patient continence, 82.4% did not use more than 1 absorbent pad in 24 h, at 6 months postoperatively. Conclusion. RALP with an initial posterior dissection to the seminal vesicle was a safe and efficient method for controlling prostate cancer, even in these initial cases.